Transportation Security Administration (TSA) Aptitude Alignment Job Role Study (JRS) for Travel Document Checker (TDC) Position. (December 2020) - Korbelak, Kristopher; Dressel, Jeffrey; Sanders, Emily; LaFreniere, Jenny; Carter, Anson
The current study investigated individual differences and their relationship to performance while fulfilling the Travel Document Checker job role at security screening checkpoints. It is part of a larger effort to understand variability in performance across different job roles that Transportation Security Officers (TSOs) routinely fulfill. Vigilance, task-focused coping and avoidance-focused coping explained the most variance in counterfeit detection. Future efforts should validate these findings and determine individual difference characteristics that are meaningful predictors of performance across other checkpoint job roles.